Invisible or Mainstream? Disability in Surveys and Censuses in Low- and Middle-Income Countries - Mitra, Sophie; Chen, Wei; Herve, Justine; Pirozzi, Sophia; Yap, Jaclyn (World Bank, Washington, DC, 2021)
This paper examines to what extent household surveys and censuses in low- and middle-income countries include disability questions and the types of questions under use. A pool of 734 data sets and 1,297 data set-years from 133 low- and middle-income countries from 2009 to 2018 were screened for disability questions, which were classified by type of questions: Washington Group short set of questions, other functional difficulty questions, activities of daily living, broad activity limitation, general disability, and other disability questions. Only 31 percent of the data sets under review had at least one disability-related question and 15 percent of the datasets of low- and middle-income countries have functional difficulty questions that meet international standards, whether the Washington Group short set or other functional difficulty questions. The most commonly found disability question is the general question “Do you have a disability?” which does not produce meaningful and internationally comparable data. The adoption of functional difficulty questions such as the Washington Group short set in national censuses and surveys and in international surveys is needed to monitor the implementation of the 2030 Agenda for Sustainable Development as well as the Convention on the Rights of Persons with Disabilities.